Black male frames : African Americans in a century of Hollywood cinema, 1903-2003 - Williams, Roland Leander, 1953- (Television and popular culture., 2015)
Black Male Frames charts the development and shifting popularity of two stereotypes of black masculinity in popular American film: "the shaman" or "the scoundrel." Starting with colonial times, Williams identifies the origins of these roles in an America where black men were forced either to defy or to defer to their white masters. These figures recur in the stories America tells about its black men, from the fictional Jim Crow and Zip Coon to historical figures such as Booker T. Washington and W. E. B. Du Bois. Williams argues that these two extremes persist today in modern Hollywood, where actors such as Sam Lucas, Paul Robeson, Sidney Poitier, Denzel Washington, and Morgan Freeman, among others, must cope with and work around such limited options. Williams situates these actors' performances of one or the other stereotype within each man's personal history and within the country's historical moment, ultimately to argue that these men are rewarded for their portrayal of the stereotypes most needed to put America's ongoing racial anxieties at ease. Reinvigorating the discussion that began with Donald Bogle's seminal work, Toms, Coons, Mulattoes, Mammies, and Bucks, Black Male Frames illuminates the ways in which individuals and the media respond to the changing racial politics in America.